Influence of the moment exerted by the athlete on the pole in pole-vaulting performance - Morlier, J.; Mesnard, M. (Journal of Biomechanics, 2007)
Current studies on pole-vaulting focus mostly on energy transfer data [Ekevad, M., Lundberg, B., 1995. Simulation of "smart" pole vaulting. Journal of Biomechanics 28, 1079-1090; Ekevad, M., Lundberg, B., 1997. Influence of pole length and stiffness on the energy conversion in pole-vaulting. Journal of Biomechanics, 30, 259-264; Linthorne, N.P., 2000. Energy loss in the pole vault take-off and the advantage of the flexible pole. Sports Engineering 3, 205-218; Schade, F., Arampatzis, A., Brüggemann, G.P., 2006. Reproducibility of energy parameters in the pole vault. Journal of Biomechanics 39, 146-147.] and often fail to take into account the actions exerted on the pole [Arampatzis, Schade, Brüggemann, 2004. Effect of the pole-human body interaction on pole-vaulting performance. Journal of Biomechanics 37, 1353-1360]. The present study integrates the 3D kinematics data of the athlete but also the actions measured at the end of the pole in the planting box and on the track during the last stride before take-off. It proposes a mechanical model allowing determination of the pole-vaulter's actions on the pole. The model is based on a global mechanical approach. The pole-vaulter's action on his upper and lower hand is concentrated on one middle point to solve the dynamics problem. The model was applied to seven experienced pole-vaulters. The force and the moment exerted on the pole by the pole-vaulter during the last stride before take off and during jump stage, were calculated. This analysis of the compressive force and bending moment for seven pole-vaulters helps to highlight the impact of the moment in the performance. The conclusion is confirmed by an additional comparative study carried out on two pole-vaulters, with comparable morphologies and performing with the same pole.